The Parent-Adolescent Relationship and Risk-Taking Behaviors Among Chinese Adolescents: The Moderating Role of Self-Control - Liu, Lu; Wang, Na; Tian, Lumei (Frontiers in Psychology, 2019)
The present study primarily aimed to examine whether self-control serves as a moderator in the associations between parent-adolescent relationships, including parental support and parent-adolescent conflict, and risk-taking behaviors among adolescents. The 917 Chinese adolescents whose mean age was 14.38 years (SD = 1.69) completed questionnaires effectively. The results indicated that the relationships between either parental support or parent-adolescent conflict and adolescent risk-taking behavior were moderated by self-control. Among those adolescents with lower levels of self-control, both higher levels of parent-adolescent conflict and lower levels of perceived parental support predicted more risk-taking behaviors, but their predicting roles got weakened with the increase of the level of self-control. Accordingly, good parent-adolescent relationship, particularly less parent-adolescent conflict, is critical for decreasing adolescent risk-taking. Otherwise, improving self-control is particularly helpful to those adolescents having more conflict with their parents or less parental support to decrease their risk-taking.